Programowanie dynamiczne w zastosowaniu do rozdziału środków finansowych w produkcji rolniczej - Skwarczyński, Antoni (Wydział Prawa i Administracji UAM, 1969)
A State Agricultural Farm which, besides other agricultural products, grows potatoes, sugar beets and rape, gets at the beginning of the planned three-year period substantial financial credit for the three, agricultural products mentioned above. A State Farm can add part of its income to the financial funds at the end of every year. A State Agricultural Farm wants to use its financial credit in the optimum way by dividing it relatively between the three agricultural products during the three connective years in order to get the total gross income from these products at the end of the planned year (three-year period). This problem has been solved by mean of dynamic programming, taking also into consideration both linear and parametrical programming in which variable parameter is the amount of financial credit.
The Application of Dynamic Programming in the Allocation of Financial Resources in Agricultural Production